Imaging at diagnosis impacts cancer‐specific survival among patients with cancer of the oropharynx. Issue 16 (1st May 2019) - Morgan, Rustain L.; Eguchi, Megan M.; Mueller, Adam C.; Daugherty, Stacie L.; Amini, Arya; Karam, Sana D.
Abstract : Background: The optimal imaging for the staging of oropharyngeal cancer is not well defined. Methods: The linked Surveillance, Epidemiology, and End Results (SEER)–Medicare database for 2006 through 2011 was used to compare patient characteristics and hospital region by the initial imaging modality used for patients with oropharyngeal cancer. The primary outcome was 3‐year cancer‐specific survival (CSS). Cox proportional hazards models were adjusted for imaging, age, sex, region, education, race, American Joint Committee on Cancer stage of disease, and treatment, which were examined using backward elimination. The authors also explored how initial imaging use varied by patient characteristics and hospital region. Results: A total of 1765 patients underwent initial diagnostic imaging. Of those, approximately 11.4% (202 patients) received computed tomography (CT) alone as their initial imaging modality, 5.2% (91 patients) underwent magnetic resonance imaging (MRI) without positron emission tomography (PET), and 83.3% (1472 patients) had initial imaging that included PET. The overall 3‐year CSS rate for the entire population was 63.7%. In the adjusted survival models compared by initial imaging modality, patients who underwent a PET examination were found to have higher survival than those who underwent CT alone or MRI, respectively (hazard ratio, 1.337 [95% CI, 1.001‐1.785; P = .0491]; and hazard ratio, 1.748 [95% CI, 1.2‐2.545; P = .0036]). Conclusions: Among patients with oropharyngeal cancer, initial staging with PET imaging was associated with improved 3‐year CSS compared with initial staging with MRI or CT. Abstract : The optimal imaging for the staging of oropharyngeal cancer is not well defined. In the current study, Surveillance, Epidemiology, and End Results‐Medicare analysis demonstrates an association between initial staging with positron emission tomography and improved cancer‐specific survival for patients with squamous cell carcinoma of the oropharynx compared with initial staging using magnetic resonance imaging alone.